Burrow ambient temperature influences Helice crab activity and availability for migratory Red‐crowned cranes Grus japonensis. Issue 20 (18th September 2020) - Li, Donglai; Zhang, Jing; Chen, Lingyu; Lloyd, Huw; Zhang, Zhengwang
Abstract: For migratory birds that specialize on particular benthic macroinvertebrate species, the timing of migration is critical since prey availability may be temporally limited and a function of local ambient temperature. Hence, variation in local ambient temperature can influence the diet composition of migrant birds, and, consequently, they may be constrained by which stopover and wintering sites they are able to utilize during periods of colder temperatures. Here, we use fecal analysis, observer‐based population counts, digital video recordings, and temperature data to test five predictions regarding the influence of local ambient temperature on the activity and availability of mudflat crabs—a key prey resource at three staging/wintering sites in eastern China, for migratory Red‐crowned cranes ( Grus japonensis ) and how this subsequently influences crane diet and use of wetland sites. Pearson's correlations and generalized linear models revealed that mudflat crabs became significantly more surface active with increasing burrow ambient temperature. Piecewise regression analysis revealed that crab surface activity was largely limited to a burrow ambient temperature threshold between 12 and 13℃ after which activity significantly increased. Crab activity declining temporally during the crane's autumn migration period but increased during spring migration. Crabs accounted for a significant proportion of crane diet at two of three sites; however, the frequency of crab remains was significantly different between sites, and between autumn and spring migration. Analyses of crane count data revealed a degree of congruence between the migration timing of Red‐crowned cranes with periods of warmer ambient temperature, and a significant, positive correlation between the percentage of crab remains in crane feces and site ambient temperature. Collectively, our data suggest that temperature‐related mudflat crab activity may provide an important time window for migratory Red‐crowned cranes to utilize critical stopover sites and the crabs' food resources. Abstract : Mudflat crabs became significantly more surface active with increasing burrow ambient temperature, and the crab surface activity was largely limited to a burrow ambient temperature threshold between 12 and 13°C after which activity significantly increased. Crabs accounted for a significant proportion of crane diet at two of three sites; however, the frequency of crab remains was significant different between sites, and between autumn and spring migration. A degree of congruence between the migration timing of Red‐crowned cranes with periods of warmer ambient temperature, and a significant, positive correlation between the percentage of crab remains in crane feces and site ambient temperature.